Experimental study on double cuneiform reamed anchorages for cable bolt boreholes in soft rock. (October 2022) - Jia, Housheng; Wang, Yinwei; Liu, Shaowei; Li, Yongen; Shao, Ruling; Wang, Guoying; Guo, Zhiqiang; Wang, Lin
Abstract: This paper deals with the problems of the low bonding force between hardened resin and soft surrounding rock, and the rapid attenuation of anchoring forces when conventional anchoring methods are used for cable bolts. The main goal of paper is to develop methods that will take full advantage of the potentially great supporting force that can be provided by high-strength cable bolts installed in soft rock. The study described in this paper discusses cuneiform reamed anchors for cable bolt boreholes. It is proposed that increasing the number of cuneiform cavities in the boreholes (with each cavity having appropriate geometric dimensions) is an effective way to prevent cable bolt anchorage failure. The results of a comparative analysis of single cuneiform reamed anchors (SCRAs) and double cuneiform reamed anchors (DCRAs) using numerical simulations are described. The simulations show that after being deformed by tensional forces of up to 200 kN, the maximum displacement of hardened resin in a DCRA borehole and the maximum plastic strain in the rock surrounding a DCRA borehole are, respectively, 50% and 46% smaller that they are for an SCRA borehole. The DCRA provides more stability and is an effective way to access the great supporting forces that a high-strength cable bolt is potentially capable of providing. The simulations were also able to determine the appropriate reaming angles for rocks of different strength. Using the simulation data, a double cuneiform reaming tool (DCRT) was developed. A field test has verified that this tool can ream two cuneiform cavities in a borehole to enlarge a section of the borehole when the tool is rotated by the drill rod. The DCRAs guarantee that cable bolts installed in soft rock will provide high supporting forces and that the cable bolts will not suffer anchoring force attenuation under severe ground pressure. Highlights: The synergistic mechanism of DCRAs was revealed, and the optimal reaming angle for different surrounding rock strengths was determined. The DCRT was developed, boreholes reamed with the DCRT can prevent the resin encasing the cable bolt from separating from surrounding rock. DCRAs allow high-strength cable bolts to take full advantage of their supporting force and minimize supporting force attenuation.